2009
DOI: 10.3201/eid1504.081358
|View full text |Cite
|
Sign up to set email alerts
|

Lobomycosis in Offshore Bottlenose Dolphins (Tursiops truncatus), North Carolina

Abstract: Lacazia loboi , a cutaneous fungus, is found in humans and dolphins from transitional tropical (Florida) and tropical (South America) regions. We report 2 cases of lobomycosis in stranded bottlenose dolphins ( Tursiops truncatus ) and 1 case of lobomycosis-like disease in 1 free-swimming, pelagic, offshore bottlenose dolphin from North Carolina, where no cases have previously been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 10 publications
4
48
0
1
Order By: Relevance
“…5), that may ulcerate 1 The disease's nomenclature of lobomycosis (or Lobo's disease) is a recommended nomen conservandum by virtue of its common usage since at least 1973 and the fact that it honours its discoverer, Jorge Lobo, who in 1931 described the first case of a chronic, cutaneous mycosis in man, which he then called keloidal blastomycosis and form plaques that may exceed 30 cm in their broadest dimension . Initially only observed in inshore/estuarine Tursiops truncatus and Sotalia guianensis, lobomycosis was recently detected in offshore T. truncatus off northern California, suggesting that its range may be expanding (Rotstein et al 2009) or that its offshore occurrence has eluded scientists to date. Dolphins may live with this progressive disease for several years (Murdoch et al 2008).…”
Section: Lobomycosismentioning
confidence: 99%
See 1 more Smart Citation
“…5), that may ulcerate 1 The disease's nomenclature of lobomycosis (or Lobo's disease) is a recommended nomen conservandum by virtue of its common usage since at least 1973 and the fact that it honours its discoverer, Jorge Lobo, who in 1931 described the first case of a chronic, cutaneous mycosis in man, which he then called keloidal blastomycosis and form plaques that may exceed 30 cm in their broadest dimension . Initially only observed in inshore/estuarine Tursiops truncatus and Sotalia guianensis, lobomycosis was recently detected in offshore T. truncatus off northern California, suggesting that its range may be expanding (Rotstein et al 2009) or that its offshore occurrence has eluded scientists to date. Dolphins may live with this progressive disease for several years (Murdoch et al 2008).…”
Section: Lobomycosismentioning
confidence: 99%
“…Whether this is due to L. loboi infection or to other causes is still uncertain (Symmers 1983). A review of the literature (Migaki et al 1971, Caldwell et al 1975, Bossart 1984, Sim玫es-Lopes et al 1993, Bossart et al 2003, Moreno et al 2008, Rotstein et al 2009) revealed that at least 11 T. truncatus (9 inshore, 2 offshore) died with advanced lobomycosis in North and South America. Besides the presence of L. loboi in the axillary lymph nodes of one specimen, none of the 5 dolphins investigated in detail had involvement of internal organs or mucous membranes.…”
Section: Lobomycosismentioning
confidence: 99%
“…Histologically, dolphin and human lesions consist of multifocal dermal granulomas with inflammatory infiltrates containing histiocytes, multinucleated giant cells, and large numbers of yeast-like cells, 6 to 12 碌m in diameter, arranged singly or in chains connected by tube-like bridges (Migaki et al 1971, Bossart 1984. While historically the lesions and causative organisms appeared morphologically similar, initial gene sequencing of the organism from dolphins suggested it was more closely related to Paracoccidioides brasiliensis than to L. loboi of hu man origin (Rotstein et al 2009). More recent molecular data from HERA dolphins and others supported these preliminary findings and show that a novel uncultivated strain of P. brasiliensis is the cause of dolphin lacaziosis/lobomycosis, which has now been renamed PC (Vilela et al 2016).…”
Section: Paracoccidioidomycosis Cetimentioning
confidence: 99%
“…Characterized by greyish, whitish to slightly pink, verrucous lesions, often in pronounced relief, that may ulcerate and form plaques, lobomycosis 2 and LLD naturally affect common bottlenose dolphins Tursiops truncatus and Guiana dolphins Sotalia guianensis from Brazil, Ecuador, Peru, Colombia, Venezuela and Suriname (de Vries and Laarman, 1973;Sim玫es-Lopes et al, 1993;Van Bressem et al, 2007;Bermudez et al, 2009;Daura-Jorge and Sim玫es-Lopes, 2011). Lobomycosis is caused by a dimorphic fungus resembling Lacazia loboi (Taborda et al, 1999;Hauboldt et al, 2000) but genetically more closely related to Paracoccidioides brasiliensis (order Onygenales, family Ajellomycetaceae) (Rotstein et al, 2009;Esperon et al, 2011;Ueda et al, 2013). LLD is 1 Moreno, I.B., Ott, P.H., Tavares, M., Oliveira, L.R., Borba, M.R., Driemeier, D., Nakashima, S.B., Heinzelmann, L.S., Siciliano, S. and Van Bressem, M-F. (2008) Mycotic dermatitis in common bottlenose dolphins (Tursiops truncatus) from southern Brazil, with a confirmed record of lobomycosis disease.…”
Section: Introductionmentioning
confidence: 99%